KEHIDUPAN SOSIAL EKONOMI PETANI BENGKOANG DI KECAMATAN KURANJI PADANG 1990-2012 - Ulfa, Eliza - (Pendidikan Sejarah, 2014)
Â This thesis diSCIsses about the life of bcngkoang farmers in district Kur.u1ji Padang, since 1990until 2012. The fonnulation of the problem in thi study !IS follows :economic life atler lhe bcn&koo.ns farming. how the influen<.."e tovr<ltd lhc social lir...: and what is m<ltivatcd the farmer.;. to plant bcngkoang .A$ n study ot the socio-econom ic hi$lOr) â¢ this thesis aims to louk at the effect of bt.-"fgk<Xtn g plants tow3:rd 54.X:ial and tXonomit.: life of society in Oistric:t Kuranji fadaog .This thesis. using historical rescruCh consists of four stages: hcurhtic ( scun;h and data collection ) â¢ source criticism ,intCl"pt"!LUJion and histor ogr.phy ( the writing ) .1990 sene a4> the beginning of the wriling limit because on that year. farmers in Â the Â f)istrict Â Kuronj i Â commun ity Â beg.311 Â to develop and grow â¢he bengkoang Â ()O each land.rrior t() LheÂ  bcngkoong Â plants .people in lhe District Kuroojirely rice planL and othc.-r hooiculture ;:rops 0.$ a source of ctlOOomics community .Commu nities in the DistrictKuranji """""" lhat cosy to plant the bctlgkoong and seed of !be bctlgkoong alsoc:hcop to buy Â â¢ In 2012 used as tt WTitin.g dJinc bca&use in this ye:lt the <!Â«line of bengkoo.ngÂ  pcoduct ()n and Â narrowing Â bcn,gkoang faming land thm has caused many residential bu ildings in lhe OiSlrict Kura.nji. The results of the study it could be concluded Â that the motivation Â of the people as bt:ng,k03ng Â farmers began Â pÂ«:>jXtgators Â art some citi1.cns whointroduced the bc..-ngkoang crop â¢ Â·me resuJts obtained from bcngkooog plants by Kuranji community in the1970s was l.he tcmpl:u for mWly communi) K urallji so in tne 19WÂ·s. many people who pn:vioosly worked as8 fanner rice. bcngkoan_g rannffi to switch into.